Design of a Problem-Solving Counseling Package for Procrastination and Comparison of Its Effectiveness with Goal-Setting Training on Improving Academic Procrastination in Students With and Without Learning Disabilities - Taghavi, Zahra; Safihoveydi, Zahra; Mousavi Armaghankhani, Nasim; Besharati, Fatemeh; Soleymani, Pari (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The purpose of this study was to design a problem-solving counseling package for procrastination and to compare its effectiveness with goal-setting training in improving academic procrastination among students with and without learning disabilities.Materials and Methods: The present study employed a quasi-experimental design with repeated measurements, including pretest, posttest, and a two-month follow-up, conducted with three groups: two experimental groups (problem-solving counseling for procrastination and goal-setting training) and one control group. The statistical population consisted of all elementary school students with varying levels of academic procrastination, including students with and without learning disabilities, during the 2025–2026 academic year in schools in Tehran. Students with learning disabilities were selected using purposive sampling, whereas students without learning disabilities were selected through simple random sampling. The research instrument was the Academic Procrastination Scale (APS). Descriptive statistics such as mean and standard deviation were used for descriptive analysis, and inferential analyses were conducted using the Kruskal–Wallis H test and repeated-measures analysis of covariance at a significance level of 0.05, using SPSS version 27.Findings: The results of the analyses indicated significant differences among the study groups in the components of inability to get things done (F(2,36)=4.82, p=0.014), attention drift (F(2,36)=3.97, p=0.026), and lack of initiative (F(2,36)=5.21, p=0.010). Post hoc analyses showed that goal-setting training was effective only in reducing inability to get things done among students without learning disabilities (p0.05). Overall, no significant difference was observed between the effectiveness of the two intervention methods on most variables.Conclusion: Overall, the findings indicate that both goal-setting training and problem-solving counseling are effective in reducing academic procrastination; however, the type and magnitude of their effects vary depending on the presence or absence of learning disabilities. Specifically, problem-solving counseling led to greater improvements in the executive and behavioral components of procrastination compared to goal-setting training. These results highlight the necessity of designing integrated interventions based on problem-solving and goal orientation to enhance academic self-regulation.